Tacrolimus alleviates LPS‐induced AKI by inhibiting TLR4/MyD88/NF‐κB signalling in mice. Issue 2 (9th December 2021) - Hu, Xueqing; Zhou, Wenqian; Wu, Shun; Wang, Rui; Luan, Zhiyong; Geng, Xin; Xu, Na; Zhang, Zhaoyong; Ruan, Zhenmin; Wang, Zenghui; Li, Furong; Yu, Chen; et al.
Abstract: Lipopolysaccharide (LPS)‐induced sepsis‐associated acute kidney injury (SA‐AKI) is a model of clinical serious care syndrome, with high morbidity and mortality. Tacrolimus (TAC), a novel immunosuppressant that inhibits inflammatory response, plays a pivotal role in kidney diseases. In this study, LPS treated mice and cultured podocytes were used as the models of SA‐AKI in vivo and in vitro, respectively. Medium‐ and high‐dose TAC administration significantly attenuated renal function and renal pathological manifestations at 12, 24 and 48 h after LPS treatment in mice. Moreover, the Toll‐like receptor 4 (TLR4)/myeloid differential protein‐88 (MyD88)/nuclear factor‐kappa (NF‐κB) signalling pathway was also dramatically inhibited by medium‐ and high‐dose TAC administration at 12, 24 and 48 h of LPS treatment mice. In addition, TAC reversed LPS‐induced podocyte cytoskeletal injury and podocyte migratory capability. Our findings indicate that TAC has protective effects against LPS‐induced AKI by inhibiting TLR4/MyD88/NF‐κB signalling pathway and podocyte dysfunction, providing another potential therapeutic effects for the LPS‐induced SA‐AKI.